Architecture’s Oedipization. The built space reason of being - Liviu Gabriel Ghiţuleasa (Urbanism. Arhitectura. Constructii, 2014)
The present paper is not intended only to debate the concept of built space, but also to highlight how this could be altered through the absence of the space term. Therefore, the signification is thus changed, so the notion that involves sacred gestures is distorted by a diminished understanding of the construction term - seen only as a multitude of material, in lack of a primary sense. Structured around the idea on how can be comprised the concept of Oedipus Syndrome (from psychoanalysis), the paper achieves a structural analysis of the system of values on which the architecture is founded. Throughout our study the problem of absence is a key concept that translates the notion of heritage, and also the latter term refers to a second point of gravity of our text. Another aspect of interest is the analysis of the question of how contemporary architecture consider the term of sense, or if in its inner is also included the notion of truth, with the assumption that a real architecture is not necessarily a true architecture.